(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article deals with the analysis of the relationship ritual and construction of religious identity. In any society there is a system of ritual and ceremonial actions which define how the semantic structure of religious identification, so its manifestation. The angle of view of religious identity is considered as one of the first in the history of forms of human identity, laid the basis for the formation of both social and ethnic identity. Religion becomes a kind of cultural code, transmitted from generation to generation, defining morality and social norms. The importance of understanding the integrity and constancy of existence in time and space that occurs in the context of the persistent religion of traditions and rituals. The first known of the history rituals associated with magical action in totemism. Totemism is due to the necessity of gaining a sense of unity, collectivism of primitive thinking, an important factor which was the ancestral identification. The analysis of the relationship of the Muslim rituals and their effect on the construction of religious identity. Key words: religion, identity, ritual, culture, Islam.Christianity, self-identity, symbol, construction of religious identity.